Pendampingan Pemahaman Materi Greeting dengan Media Video Scribe di MTs Tauhidiyah Bojonegoro - Rohmat Hidayat; Anggi Indah Yuliana; Ro’ikhatul Miskiyah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
The purpose of this community service activity for the Appropriate Technology Application Program is to be able to take advantage of the development of Video Scribe learning media to improve understanding of English material, Greeting, for class VII. Partners for community service activities, assisting in understanding Greeting material with Video Scribe media, are MTs Tauhidiyah, Senganten village, Gondang sub-district, Bojonegoro. Participants focused on class VII students with a total of 35 remaining. Based on the implementation of PPTTG activities in Senganten village, this service learning method is considered the most relevant to PPTTG in the field of education. The results of these activities show that 35 students' average score before using the media is 29.71, while the average score after students use the media is 70.00 this count is calculated using Google form. So it can be concluded based on the assessment criteria that there are significant differences before students using the media with students after using the media. Student feedback on the greeting material learning activities also affects the effectiveness of learning speaking skills. The application using the demonstrator method shows that students in the class are very enthusiastic and actively interact with us during learning. In addition, the use of these media can improve students' understanding of the material. participants or audience enthusiastic in participating in this activity. Based on the results of community service activities or MTs Schools in the PKM-PPTTG scheme, it can be concluded as follows: the application of Video Scribe media in PKM-PPTTG Mentoring Understanding of Greeting Materials is a variety of learning methods to create an interesting, creative, and interesting learning atmosphere innovative and the results of the application of this TTG can improve students' understanding of the greeting material. This can be shown by the results of the average value of the posttest being higher than the pretest.